ACTIVATING THE SACRED IN THE RELIGIOUS TOURIST TRIP REVIEW ARTICLE - Ahmed Obaid Oraibi (American Journals Publishing, 2024)
This research will discuss several important points that will be divided into four topics:First topic will discuss (The tourist trip design).Second topic will discuss (happy tourist or passenger).Third topic will discuss (Satisfaction Measurement).Forth topic will discuss (Religious behavior)and we will explain the importance of each point the first topic will focus on the (TOI) and the section that the trip goes through , the second topic will focus on how to become happy and the important factors to raise the tourist or passengers levels of happiness , the third topic will focus on how to measure the tourist or the passengers correctly , the forth topic will discuss the importunes of the religious behavior in the tourist trip.
Keywords: Tourist trip design, religious tourism, tool of interest, religious behavior.